Sustainable Maritime Transportation and Exploitation of Sea Resources - Rizzuto, Enrico; Soares, C. Guedes (CRC Press, 2011)
Sustainable Maritime Transportation and Exploitation of Sea Resources covers the most updated aspects of maritime transports and of coastal and sea resources exploitation, with a focus on (but not limited to) the Mediterranean area. Vessels for transportation are analysed from the viewpoint of ship design in terms of hydrodynamic, structural and plant optimisation, as well as from the perspective of construction, maintenance, operation and logistics. The exploitation of marine and coastal resources is covered in terms of fishing, aquaculture and renewable energy production as well as of subsea.